2012
DOI: 10.1038/ejhg.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of SIGMAR1 as a cause of familial ALS with dementia

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron diseases (MND), while frontotemporal lobar degeneration (FTLD) is the second most common cause of early-onset dementia. Many ALS families segregating FTLD have been reported, particularly over the last decade. Recently, mutations in TARDBP, FUS/TLS, and C9ORF72 have been identified in both ALS and FTLD patients, while mutations in VCP, a FTLD associated gene, have been found in ALS families. Distinct variants located in the 3 0 -untranslated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Those results support the notion that Sig-1Rs, by interacting with endogenous myristic acid, play a pivotal role in the p35 myristoylation and degradation. Discussion Sig-1Rs have been reported to play a role in the pathogenesis of neurodegenerative disorders including AD (30,45,46), Parkinson's disease (47,48), and motor neuron disorders (49)(50)(51). The underlying molecular mechanisms of Sig-1R action remain to be totally clarified.…”
Section: Sig-1r Controls P35 Degradation Mainly Through the Proteasomalmentioning
confidence: 97%
“…Those results support the notion that Sig-1Rs, by interacting with endogenous myristic acid, play a pivotal role in the p35 myristoylation and degradation. Discussion Sig-1Rs have been reported to play a role in the pathogenesis of neurodegenerative disorders including AD (30,45,46), Parkinson's disease (47,48), and motor neuron disorders (49)(50)(51). The underlying molecular mechanisms of Sig-1R action remain to be totally clarified.…”
Section: Sig-1r Controls P35 Degradation Mainly Through the Proteasomalmentioning
confidence: 97%
“…Finally, several 3′ UTR variants and a missense mutation in SIGMAR1 gene are reported in ALS and FTLD patients [11][12][13]. Interestingly, some 3′ UTR variants (c.672*51GNT and c.672*43GNT) but not the c.672*26CNT substitution co-segregate with hexanucleotide repeat expansions in C9ORF72, and those two variants are likely not responsible for the onset of ALS or FTLD [12,63].…”
Section: Mitochondria Ermentioning
confidence: 98%
“…These variants (c.672*51GNT, c.672*26CNT and c.672*47GNA) were associated with dysregulated SIGMAR1 transcription. Meanwhile, Belzil et al reported a different SIGMAR1 variant (c.672*43GNT) in Caucasian ALS patients who showed cognitive deficits [12]. In addition, a missense SIGMAR1 mutation (c.304GNC), which results in substitution of glutamine for glutamic acid at amino acid residue 102 (p.E102Q), was reported in familial ALS patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Expression profiles of these variants showed that there was an alteration in SIGMAR1 transcription. Another variant of SIGMAR1 gene (c.672*43G>T) was found in Caucasian ALS patients with cognitive deficits but was also found in one control after screening in a healthy population [16]. In addition, a missense SIGMAR1 mutation (c.304G>C), which results in the substitution of glutamine for glutamic acid (p.E102Q) in the highly conserved transmembrane domain of SIGMAR1, was identified in three families of fALS-FTLD showing autosomal dominant pattern.…”
Section: Discussionmentioning
confidence: 93%
“…3′-UTR variants of SIGMAR1 have been found associated with ALS-FLTD in both autosomal dominant form and sporadic cases [4]. In another study, the SIGMAR1 3′-UTR region in Caucasian ALS patients was investigated along with a repeat expansion in C9ORF72 [16]. Previously, C9ORF72 repeat expansions were reported in FTLD and fALS [17,18].…”
Section: Introductionmentioning
confidence: 98%